2008
DOI: 10.3354/cr00759
|View full text |Cite
|
Sign up to set email alerts
|

Structure and trends in climate parameters affecting winegrape production in northeast Spain

Abstract: This study examined the structure and trends of climate parameters important to winegrape production from 1952 to 2006 in the Alt Penedès, Priorat, and Segrià regions of NE Spain. Average and extreme temperature and precipitation characteristics from 3 stations in the regions were organized into annual, growing season, and phenological growth stage periods and used to assess potential impacts on vineyard and wine quality, and changes in varietal suitability. Results show an overall growing season warming of 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
107
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 53 publications
9
107
0
2
Order By: Relevance
“…However, due to the high infiltration capacity of the soils studied, in which there was no surface runoff despite the steep slopes (Abreu, 2005), the most relevant effect was that related to the amount of nitrate leached. The quantities of water applied were similar to those from the rainfall events that normally occur in the study area (Ramos et al, 2008). Over the last 10 years, 7-9 events bearing total rainfall of between 25 and 50 mm have been recorded every year (some extreme events have produced more than 75 mm, with a 2-year return period).…”
Section: Discussionsupporting
confidence: 55%
“…However, due to the high infiltration capacity of the soils studied, in which there was no surface runoff despite the steep slopes (Abreu, 2005), the most relevant effect was that related to the amount of nitrate leached. The quantities of water applied were similar to those from the rainfall events that normally occur in the study area (Ramos et al, 2008). Over the last 10 years, 7-9 events bearing total rainfall of between 25 and 50 mm have been recorded every year (some extreme events have produced more than 75 mm, with a 2-year return period).…”
Section: Discussionsupporting
confidence: 55%
“…There was a strong correlation between the total acidity and HI for all studied varieties ( Figure 5). In other studies it was observed that warmer growing season results in the earlier harvest date, lower production, higher quality of wine and vintage rating ( Jones et al 2005, Blanco-Ward et al 2007, Ramos et al 2008.…”
Section: Resultsmentioning
confidence: 91%
“…The impact of warming was found to be negative and reduced winegrape quality, which varied from region to region (Webb et al 2008). Increases in yield variability in the warmest vintages were found by Ramos et al (2008) and Keller (2010). Hot summers result in earlier grape ripening and vintages and in some wine-growing regions botrytis is more likely to appear (Petgen 2007, Prior 2007.…”
mentioning
confidence: 99%
“…In Mediterranean regions, changes in the rainfall inter-seasonal distribution have been observed and evaluated in vineyards, indicating potential soil moisture stress during the critical growth stages of the grapevines [53].…”
Section: Soil Moisture Dynamicsmentioning
confidence: 99%